Microfluidic-Based Droplets for Advanced Regenerative Medicine: Current Challenges and Future Trends - Hojjatollah Nazari; Asieh Heirani-Tabasi; Sadegh Ghorbani; Hossein Eyni; Sajad Razavi Bazaz; Maryam Khayati; Fatemeh Gheidari; Keyvan Moradpour; Mousa Kehtari; Seyed Mohsen Ahmadi Tafti; Seyed Hossein Ahmadi Tafti; Majid Ebrahimi Warkiani (Biosensors, 2021)
Microfluidics is a promising approach for the facile and large-scale fabrication of monodispersed droplets for various applications in biomedicine. This technology has demonstrated great potential to address the limitations of regenerative medicine. Microfluidics provides safe, accurate, reliable, and cost-effective methods for encapsulating different stem cells, gametes, biomaterials, biomolecules, reagents, genes, and nanoparticles inside picoliter-sized droplets or droplet-derived microgels for different applications. Moreover, microenvironments made using such droplets can mimic niches of stem cells for cell therapy purposes, simulate native extracellular matrix (ECM) for tissue engineering applications, and remove challenges in cell encapsulation and three-dimensional (3D) culture methods. The fabrication of droplets using microfluidics also provides controllable microenvironments for manipulating gametes, fertilization, and embryo cultures for reproductive medicine. This review focuses on the relevant studies, and the latest progress in applying droplets in stem cell therapy, tissue engineering, reproductive biology, and gene therapy are separately evaluated. In the end, we discuss the challenges ahead in the field of microfluidics-based droplets for advanced regenerative medicine.